Endoscopic Retrograde Cholangiopancreatography with an Ultra-Slim Forward-Viewing Gastroscope in a 3.8 kg Infant: A Case-Report - Maria Inês Canha; Rita Prata; Pedro Martins; Gonçalo Ramos; Rui Alves; Isabel Afonso; António Mateus Dias; João Coimbra (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Experience with pediatric endoscopic retrograde cholangiopancreatography (ERCP), particularly in infants, is limited. The lower incidence of biliopancreatic disorders in infants and the discontinuation of pediatric duodenoscopes raise concerns regarding ERCP’s technical efficacy and safety in this vulnerable population, for whom conventional duodenoscopes are not recommended. Short case description: We report the case of a low-weight infant with short bowel syndrome under parenteral nutrition, who was referred for ERCP due to choledocholithiasis with progressive jaundice. We opted for an ultra-slim forward viewing gastroscope (5.4mm distal end outer diameter and 2.2mm working channel) with a needle knife sphincterotome (1.8mm outer sheath diameter). This allowed sphincterotomy with adequate gallstone removal and complete normalization of cholestasis parameters without associated complications. Discussion and conclusion: With this case we aimed to describe a previously unreported approach to a low-weight infant with gallstone disease requiring ERCP, which proved to be safe and effective.